(untitled) (Eurasian Medical Research Periodical, 2022)
This article discusses the factors influencing the occurrence of infertility in women, the main types and diagnosis, as well as methods of treatment. Female infertility is a special condition of the reproductive system in which conception does not occur with regular unprotected sex for 12 months, and for women over 35 years - for 6 months